2021
DOI: 10.3390/ijerph18105131
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Prolonged Post-COVID-19 Symptoms and Their Implications on Dental Management

Abstract: The available data regarding the short and long-term consequences of COVID-19 is still insufficient. This narrative review aims to provide information on the prolonged COVID-19 symptoms in recovered patients and their implications during dental management. Additionally, this manuscript highlights the oral manifestations of COVID-19 and its management. A systematic search was conducted in PubMed, Embase, Cochrane Library and Web of Science databases, WHO and CDC websites, and grey literature was searched throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 58 publications
0
25
0
1
Order By: Relevance
“…It might also make it easier to resolve emergency orthodontic problems and help to decide whether the patient can solve the problem at home or needs an emergency visit. The authors advise to first try and find a solution to the problem remotely [ 5 ]; the online triage for the post-COVID-19 patients could also facilitate work at dental offices [ 35 ]. A useful solution might be, for example, WhatsApp messenger, used by 83.8% patients in the Brazilian study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It might also make it easier to resolve emergency orthodontic problems and help to decide whether the patient can solve the problem at home or needs an emergency visit. The authors advise to first try and find a solution to the problem remotely [ 5 ]; the online triage for the post-COVID-19 patients could also facilitate work at dental offices [ 35 ]. A useful solution might be, for example, WhatsApp messenger, used by 83.8% patients in the Brazilian study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies reported on their dental treatment needs, it is important to bear in mind that protective measures should be applied not only for presumed COVID-19 patients but also for post-COVID-19 patients with or without prolonged symptoms [35].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review described the COVID-19 as an infectious disease that primarily affects the lungs. Its multi-organ involvement is responsible for several prolonged symptoms, including oral implications [ 29 , 30 ]. In recovered patients, the prolonged symptoms can delay the elective treatments.…”
Section: Discussionmentioning
confidence: 99%